1997
DOI: 10.1021/ja962780a
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Prolines as a Molecular Hinge:  Reversible Induction ofcisAmide Bonds into Peptide Backbones

Abstract: Serine, threonine-derived (4S)-oxazolidine-4-carboxylic acid, and cysteine-derived (4R)-thiazolidinecarboxylic acid, denoted pseudo-proline (Xaa[ΨR 1 ,R 2 pro]), serve as structure disrupting, solubilizing building blocks in peptide synthesis. Variation of the 2-C substituents within the heterocyclic system results in different physicochemical and conformational properties. NMR studies of a series of pseudo-proline (ΨPro)-containing peptides reveal a pronounced effect of the 2-C substituents upon the cis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 39 publications
8
148
1
2
Order By: Relevance
“…We positioned Val, Phe, and Gly in the Xaa position to examine the effect the Xaa side chain had on the cis:trans ratio of the Xaa-Thr( Me,Me pro) amide bond. We included four d-allo-threonine derivatives (5, 6, 9, and 12) because, while the influence of inverting the relative stereochemistry at the α-position of the residue preceding a Thr( Me,Me pro) has been reported, [4] the effect of changing the relative stereochemistry between the α-and β-positions on Thr( Me,Me pro) formation and conformation has not been previously investigated. Our standard conditions for the synthesis of XaaThr( Me,Me pro) derivatives involve treatment of the Thrcontaining dipeptides with 2-methoxypropene at 0 • C in the presence of an acid catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We positioned Val, Phe, and Gly in the Xaa position to examine the effect the Xaa side chain had on the cis:trans ratio of the Xaa-Thr( Me,Me pro) amide bond. We included four d-allo-threonine derivatives (5, 6, 9, and 12) because, while the influence of inverting the relative stereochemistry at the α-position of the residue preceding a Thr( Me,Me pro) has been reported, [4] the effect of changing the relative stereochemistry between the α-and β-positions on Thr( Me,Me pro) formation and conformation has not been previously investigated. Our standard conditions for the synthesis of XaaThr( Me,Me pro) derivatives involve treatment of the Thrcontaining dipeptides with 2-methoxypropene at 0 • C in the presence of an acid catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…These modified amino acid residues were introduced by Mutter and coworkers as temporary protecting groups for peptide synthesis and were found to exert a pronounced effect on the peptide backbone conformation. [1,2] The oxazolidine derivatives are now extensively used as tools to impart better solubility to a growing peptide chain in solid-phase synthesis because they prevent aggregation of growing peptide chains [3,4] and have been found to significantly increase the yields of difficult peptide sequences [5][6][7][8][9] by improving solvation and peptide coupling kinetics. This is attributed to a conformational preference for cis-amide bond formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Pro residues can experience cistrans interconversion or function as a molecular ''hinge'' within polypeptide sequence segments 31,41,42,45 and that TFE affects these parameters. 28,29,33,38 Hence, this responsiveness to TFE indicates that this second group of Pro residues act as folding enhancers and play an important role in the structure and dynamics 31,41,42,45 of the intrinsically disordered protein, rP172. These Pro residues may also be responsible for the increased level of conformational exchange observed in the 70-rP172 sample relative to AQ-rP172 as evidenced by the presence of additional HSQC crosspeaks in 70-rP172 ( Figure S1, Electronic Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…1 ppm 9,36,37 we find that only a limited set of seven Pro residues (P2, N-terminus; P127, P130, P139, P154, central domain; P157, P162, C-terminus) respond to TFE, with the largest effects observed within the C-terminal half of this protein. Since the Pro imido ring Ca and Cb chemical shifts are sensitive to polypeptide backbone conformation, 38,41,42 we infer that TFE has a select effect on the conformation of these particular prolines, but that the remaining detectable Pro residues within rP172 are resistant to TFE-induced conformational change.…”
Section: Localization Of Folding Within Rp172mentioning
confidence: 95%